How Preschool Children Recognize Hanzi? Exploring the Impact of Home Literacy Environments on Montessori Preschool Children’s Hanzi Recognition Performance - Mei-Ling Wang; Hsiao-Fang Lin; Teng-Chien Yu (SAGE Open)
This study explores the relationship between the Hanzi recognition performance and the home literacy environments of 351 children aged 3 to 6 based on Montessori’s philosophy of education. This study used 200 frequently spoken words in Montessori classrooms as the word set of a Hanzi recognition test, based on which studies at six Montessori preschools in middle and southern Taiwan were conducted. The results of this study revealed that girls’ scores are significantly higher than that of boys on the word recognition test, whereas no significant difference between the middle (4s/5s) and junior (3s/4s) classes children were observed. However, from the qualitative analysis perspective, the junior class children also performed exceptionally well. Parent-child shared reading and chats, directly and indirectly, affected their children’s Hanzi recognition outcome. The analysis of the interviews with the children suggested that family life experiences were indeed a crucial factor in the children’s word recognition.